Dog-Assisted Therapy for Children and Adolescents With Fetal Alcohol Spectrum Disorders a Randomized Controlled Pilot Study - Vidal, Raquel; Vidal, Laura; Ristol, Francesc; Domènec, Eva; Segú, Marta; Vico, Cristina; Gomez-Barros, Núria; Ramos-Quiroga, Josep Antoni (Frontiers in Psychology, 2020)
Objective The rationale of this study was to evaluate the efficacy of dog-assisted therapy (DAT) combined with pharmacological treatment in children and adolescents with fetal alcohol spectrum disorder (FASD). Method We conducted a randomized, rater-blinded, controlled pilot trial in a cohort of 33 children and adolescents with FASD. Participants were randomly assigned either to DAT group (n = 17) or Treatment as Usual (TAU control group) (n = 16). Results Of the initial 39 participants enrolled, 33 completed treatment. A mixed-effects model analysis revealed that participants who were assigned to the DAT group experienced significantly improvements on social skills (SSIS-P social skills: p = 0.02, d = 0.8), reductions on externalizing symptoms (CBCL externalizing: p = 0.03; d = 0.56), and lower scores on FASD severity (CGI-S clinician: p = 0.001, d = 0.5). Conclusion DAT is a promising adjunctive treatment for children and adolescents with FASD. Clinical Trial Registration Dog-assisted therapy for children and adolescents with fetal alcohol spectrum disorders: a randomized controlled pilot study; http://clinicaltrials.gov/, identifier NCT04038164.